Zakat Program for Post-Pandemic Economic Recovery: Qualitative Approach using Nvivo - Sunarya, Silma Lafifa; Rusydiana, Aam Slamet (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2022)
Abstract: Introduction/Main Objectives: This study aims to determine the development of research related to the practice of zakat a program for restoring the economy, where zakat is one of the Islamic financial instruments that can break the chain of poverty and build prosperity. Background Problems: The global economic crisis due to COVID-19 has caused concern for the world. Not only that, Covid-19 caused an increased number of mustahik because people have lost their jobs. Novelty: The zakat program can be used solution in post-pandemic economic recovery while maintaining environmental balance Research Methods: The method used qualitative using secondary data in the form of articles published in Dimensions period 1970-2022, then analyzed using Nvivo 12 Plus software. Finding/Results: The findings of this study indicate an increasing trend of research related to zakat as one of the financing instruments in Islamic economics. Of the 500 published articles, most stated the potential of zakat in the economy, both in economic growth, community welfare, and others. Conclusion: This research expects to help expand academic studies related to zakat and economic recovery to achieve sustainable development goals. Further research and how zakat can be a best practice program in restoring the economy is highly recommended.Keywords: Zakat, Covid-19, Economic Recovery, Nvivo 12 Plus